2016
DOI: 10.1080/15583058.2016.1154114
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Facade Walls of Existing Adobe Buildings

Abstract: Adobe construction was very common in Aveiro district, Portugal, until the middle of the 20th century. At present, there are still many adobe buildings in use, a significant percentage of which have social, cultural, and architectural value. Many of these buildings, however, are in a poor state of conservation. The existing problems are partially the result of a lack of knowledge about the materials and building systems traditionally used. To contribute to this knowledge, a visual and dimensional inspection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The factor that led to the upsurge in adobe as a construction material of choice, especially in the central region, is credited to the Art Nouveau movement that spread across Europe in various forms. This movement had a significant influence in some Portuguese cities [18], particularly in Aveiro, where it is estimated that 30-40% of the buildings are still adobe buildings [19]. The Southern region of Algarve, where the seismic hazard is relatively high [20], has a high density of adobe buildings, as shown in Figure 1.…”
Section: Characterization Of Adobe Buildings In Portugalmentioning
confidence: 99%
See 1 more Smart Citation
“…The factor that led to the upsurge in adobe as a construction material of choice, especially in the central region, is credited to the Art Nouveau movement that spread across Europe in various forms. This movement had a significant influence in some Portuguese cities [18], particularly in Aveiro, where it is estimated that 30-40% of the buildings are still adobe buildings [19]. The Southern region of Algarve, where the seismic hazard is relatively high [20], has a high density of adobe buildings, as shown in Figure 1.…”
Section: Characterization Of Adobe Buildings In Portugalmentioning
confidence: 99%
“…Three building surveys pertaining to earth-based buildings in continental Portugal were examined in this study, namely, the Algarve survey report [21], the Alentejo survey report [22], and the survey of façade walls in Aveiro [19]. From these surveys, it was concluded that it was essential to segregate these earthen buildings according to the primary, secondary, and tertiary construction material that was used to build the external walls and then the internal walls, respectively.…”
Section: Database Of Adobe Buildings Informationmentioning
confidence: 99%
“…A series of recent interventions in earthen heritage have used cement plasters as a solution for water protection resulting in disastrous consequences. Cracking, detachment, and efflorescences are some of the main degradation phenomena induced in earthen structures when covered by this type of plaster [37]. Cementitious coatings are incompatible with earthen materials, since it blocks the normal humidity cycles and promotes more damage in the original layers [36].…”
Section: Surface Protection Of Earthen Materialsmentioning
confidence: 99%
“…Samples from case study 267 show a standard deviation far superior to the other samples which confirms the higher heterogeneity of the material that was previously visualized. Silveira et al (2016) for stabilized adobe in the Aveiro region (Table 1). These values are both lower and higher than the ones obtained for Caramel´s adobe, being generally higher, with a global value of 1764±268 kg/m 3 for the three case studies.…”
Section: Bulk Density and Ultrasonic Pulse Velocitymentioning
confidence: 99%
“…Until the end of the first half of the 20th century, adobe masonry construction was very popular in several regions of Portugal, being used for external and internal walls, as is the case of the Aveiro (Silveira, Varum, and Costa, 2016) or Leiria region (Parracha et al, 2019). Masonries were also layered with an earth mortar, similar to the material of the adobe masonry, with the objective of achieving a better interaction between the different materials (Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%